Analisis Jabatan Dalam Penempatan Pegawai Pada Badan Kepegawaian Daerah Provinsi Lampung - Kasakean, Dandung; Atika, Dewie Brima; Apandi, Apandi (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2025)
Human resources are a very important asset in an organization. Human resources, namely employees, of course have different educational backgrounds and experiences that are brought into the organization. Before an organization selects employees who will occupy positions, it is necessary to first carry out a job analysis to find out what jobs must be done, how many employees are needed, and also what kind of employee specifications are suitable for a position. The problem found in the analysis of the implementation of positions at the Lampung Province Regional Civil Service Agency in 2021 is the large number of employee needs and also the large number of vacant positions. This research aims to obtain an in-depth description and analysis regarding the analysis of job implementation at the Lampung Province Regional Civil Service Agency in 2021 and also identify supporting factors and obstacles experienced during the implementation of job analysis. Researchers use qualitative research with descriptive analysis with data sources including: documentation, interviews and observation. The research results were analyzed using Dessler's (2013) job model analysis, namely analyzing Job Descriptions, Job Specifications, Determining Position Responsibilities (Responsibility & Duties), Relationships, Working Conditions. The results of the research show that the implementation Job analysis has been carried out in accordance with existing regulations, then the implementation has used the Job Analysis Management Information System (SIMANJA) application. The results of the Job Analysis carried out are in accordance with regulatory provisions and the information presented is relatively clear, however there is some information that needs to be reviewed.